Study protocol for a hybrid type 1 effectiveness-implementation trial testing virtual tobacco treatment in oncology practices [Smokefree Support Study 2.0] - Brett M. Goshe; Autumn W. Rasmussen; Lynne I. Wagner; JoRean D. Sicks; Ilana F. Gareen; Ruth C. Carlos; Benjamin A. Herman; Angela Wangari Walter; Susan Regan; Douglas E. Levy; Irene Mahon; Alona Muzikansky; et al. (BMC, 2022)
Abstract Background Persistent smoking among patients diagnosed with cancer is associated with adverse clinical outcomes, yet an evidence-based tobacco use intervention has not been well-integrated into cancer care in community oncology settings. This paper describes the protocol of a nation-wide clinical trial conducted by the ECOG-ACRIN National Cancer Institute (NCI) Community Oncology Research Program (NCORP) Research Base to assess the effectiveness of a virtual tobacco treatment intervention and the process of implementing tobacco treatment in NCORP community oncology settings. Methods/design This two-arm, multisite (n: 49 NCORP sites) hybrid type 1 effectiveness-implementation randomized controlled trial compares the effectiveness of a Virtual Intervention Treatment (VIT) versus an Enhanced Usual Control (EUC) among English and Spanish speaking patients recently diagnosed with cancer, reporting current smoking and receiving care at a participating NCORP Community or Minority/Underserved Site. The VIT includes up to 11 virtual counseling sessions with a tobacco treatment specialist and up to 12 weeks of nicotine replacement therapy (NRT). The EUC arm receives a referral to the NCI Quitline. The primary study outcome is biochemically confirmed 7-day point prevalence smoking abstinence. Moderators of treatment effect will be assessed. The study evaluates implementation processes from participating NCORP site staff via survey, administrative, and focus group data, including reach, acceptability, appropriateness, fidelity, feasibility, adoption, cost and sustainability outcomes. Discussion This trial will generate findings about the effectiveness of an evidence-based virtual tobacco treatment intervention targeting patients diagnosed with cancer and illuminate barriers and facilitators that influence implementing tobacco treatment into community oncology settings nationally. In the era of COVID-19, virtual care solutions are vital for maximizing access and utilization of tobacco treatment delivery. Trial registration ClinicalTrials.gov (NCT03808818) on January 18th, 2019; Last update posted: May 21st, 2020.